2009
DOI: 10.1111/j.1469-0691.2008.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening and cultivation of Ehrlichia canis from refrigerated carrier blood

Abstract: Improved detection and isolation of rickettsial agents from naturally infected dogs would facilitate understanding the epidemiologic roles of these hosts. In this study, current methods were refined for rapid screening of carrier blood and ticks for Ehrlichia canis, and the feasibility of blood culture after PCR screening was addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Samples were incubated at 94°C for 2 min, followed by 75 cycles at 94, 65, and 72°C for 30 s each, with a final extension for 7 min at 72°C. Positive controls consisted of 10 pg of DNA extracted from E. canis-infected DH82 cell cultures that were prepared as previously described (6,35) while negative controls consisted of preinoculation canine blood and unexposed ticks. No-template controls served as tests for contamination for every assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were incubated at 94°C for 2 min, followed by 75 cycles at 94, 65, and 72°C for 30 s each, with a final extension for 7 min at 72°C. Positive controls consisted of 10 pg of DNA extracted from E. canis-infected DH82 cell cultures that were prepared as previously described (6,35) while negative controls consisted of preinoculation canine blood and unexposed ticks. No-template controls served as tests for contamination for every assay.…”
Section: Methodsmentioning
confidence: 99%
“…A p30-based PCR assay was used to test for the presence of E. canis DNA as previously described elsewhere, with some modifications (6,35,42,43,47). Briefly, 25-l reaction mixtures were prepared with 2% dimethyl sulfoxide (DMSO), 2.0 mM MgCl 2 , 200 M of each deoxynucleoside triphosphate (dNTP), 0.3 M (each) of primers ECA30-384S (ATAAACACGCTGACTTT ACTGTTCC) and ECA30-583A (GTGATGAGATAGAGCGCAGTACC), and 0.03 U/l of Platinum Taq polymerase (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although doxycycline can successfully clear E. canis infection when administered for 4 weeks, another study [38] reported persisting abnormalities of the liver and kidney through ultrasonography after treatment. Mcclure et al [39] reported that the treatment of dogs with acute or subclinical CME with doxycycline for 28 days resulted in them becoming PCR negative for E. canis along with improved clinical parameters. Nevertheless, in the chronic CME cases in this study, there were still abnormalities in hematology, serum chemistry profiles, and ultrasonographic changes in the liver, kidney, and spleen after treatment with doxycycline for 28 days.…”
Section: E Canis=ehrlichia Canismentioning
confidence: 99%
“…A dichotomous key was used to identify four adult male and two adult female ticks, which were then bisected along the sagittal plane, pooled and placed on dry ice for template isolation. Nucleic acids were extracted from buffy coat and tick samples with the High Pure Viral Nucleic Acid kit (Roche) as previously described (McClure et al, 2009). Spleen samples were thawed on ice and nucleic acids were isolated from 10 mg portions with the DNeasy Blood & Tissue kit (Qiagen) according to the manufacturer's instructions.…”
Section: Pcr Assays For E Chaffeensismentioning
confidence: 99%